LOGO MAKER APP USER INTERFACE ANALYSIS - Irfan Irfan; Satriadi Satriadi; Jalil Jalil (Universitas Negeri Makassar, 2022)
This research seeks to provide an overview of the quality of the user interface in logo maker applications. The results of this analysis can be used to consider users in choosing applications, especially MSME actors in designing the visual identity of their products. The user interface analysis used is reviewed from the aspects of clarity, conciseness, familiarity, responsiveness, consistency, aesthetics, efficiency, and forgiveness. The results of the analysis show that these criteria show good results so that the two applications are suitable for use by UMKM actors in creating logos or other visual identities for their products.